KOMUNIKASI ANTAR NODE MELALUI BLUETOOTH UNTUK MONITORING KELEMBABAN TANAH DAN SUHU PADA GREENHOUSE BERBASIS MIKROKONTROLER - Milendy Arifputra Pamungkas; Onny Setyawati; Raden Arief Setyawan (Jurnal Mahasiswa TEUB, 2022)
Greenhouse is one of the modern methods of plant cultivation by manipulating environmental conditions according to the desired conditions. To produce healthy and fertile greenhouse plants, several factors are needed, such as temperature, sunlight, water, and soil moisture according to the type of plant. In this study, the design of a sensor node system was carried out as a monitoring of soil moisture and temperature in the greenhouse. In this design, the DHT22 sensor is used as a temperature and humidity detector, capacitive soil moisture sensor SEN0193 as a greenhouse plant soil moisture detector. The readings from the sensor will be processed by the ESP32 microcontroller so that it can be understood by the user, then sends the data to the pump controller node as input in the form of sensor data. The test was carried out several times to find that the output data from the sensor node was data that was in accordance with the circumstances. The soil moisture sensor test SEN0193 was compared with a 4 in 1 soil meter to obtain an average error of 1.15%. The DHT22 temperature sensor test was compared with a temperature thermometer